EFEKTIVITAS MEDIA GAMBAR EKSPRESI DIDUKUNG METODE DEMONSTRASI TERHADAP KETERAMPILAN MEMBACA PUISI SISWA KELAS IV SEKOLAH DASAR - Dwinata, Anggara; Hardinanto, Eko; Rahma Pratiwi, Emy Yunita; Puspitasari, Indah; Abdurochman, Abdurochman (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
The role of Indonesian language learning in elementary schools is very fundamental. Indonesian is a mandatory subject for elementary school students to study. One of the Indonesian language subjects that is often interesting and must be maximized is the skill of reading poetry. Students' poetry reading skills must be taught through providing interesting media and appropriate learning methods. The relevant media and methods are image expression media and demonstration methods. This research aims to determine the effect of expressive image media supported by demonstration methods on poetry reading skills. The research approach used is a quantitative study using true experimental design by providing treatment to one of the classes. The research was conducted on fourth grade students at SD Modern Paramadina Kediri. Data collection techniques using tests, observation and documentation. Data analysis uses prerequisite tests for normality and homogeneity, while hypothesis verification uses the t-test. The research results prove that the significance value obtained was 0.003 0.05 (5%) and the t-count value was 3.070 which was higher than the t-table value of 1.996. So it can be concluded that there is an influence of expressive image media supported by the demonstration method on the poetry reading skills of class IV students at SD Modern Paramadina Kediri.